Parental Involvement in Special Education: Collaborative Approaches for Supporting Student Success - Prof. Adrian C. Walker (ROSSIISKAYA ISTORIYA, 2026)
Parental involvement plays a crucial role in the success of students with disabilities in special education settings. collaborative approaches for fostering effective partnerships between parents, educators, and other stakeholders to support the academic, social, and emotional needs of students with disabilities. Drawing on research and best practices, this paper examines the benefits of parental involvement, strategies for promoting collaboration, and the importance of communication, empowerment, and advocacy in special education. Additionally, it discusses challenges and barriers to parental involvement and offers recommendations for overcoming these obstacles to ensure that parents are active participants in the educational process. Ultimately, this paper highlights the significance of collaborative partnerships in promoting student success and achieving positive outcomes in special education.